Chagas disease cases diagnosed in Lima - Cornejo Donayre, Alberto (1963)
Fourteen cases of Chagas disease were discovered by complementfixation tests among 214 residents of Lima who had come from endemic areas of Peru. Xenodiagnostic tests conformed that six had Trypanosoma cruzi in the ciculating blood many years after leaving an endemic area. In view of the known establishment of the vector, Trianoma infestans, in certain districts of Lima and the great number of people who are leaving endemic areas to settle in the city, there in clearly indicated a danger of creating new endemic foci in Lima.